2020
DOI: 10.1021/acscentsci.0c00068
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking Natural Human Hair Pigmentation with Synthetic Melanin

Abstract: Human hair is naturally colored by melanin pigments, which afford myriad colors from black, to brown, to red depending on the chemical structures and specific blends. In recent decades, synthetic efforts have centered on dopamine oxidation to polydopamine, an effective eumelanin similar to the one found in humans. To date, only a few attempts at polydopamine deposition on human hair have been reported, and their translation to widespread usage and potential commercialization is still hampered by the harsh cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 47 publications
1
88
0
Order By: Relevance
“…It should be also highlighted that this innovative hair dye possessed three additional features: strong adhesion capacity, as it faded only slightly after 30 washes, thermal insulation performance and incredible antibacterial performance. Differently from the previous approaches, Battistella et al suggested a metal-free PDA-based long-lasting hair coloration method was, which was not only cost-efficient, but also was carried out under mild conditions [ 246 ]. According to the study, PDA was efficiently deposed on human hair without the need of metal chelators or strong oxidants and different colors were achieved just by tuning the reaction conditions.…”
Section: Mnp and Nanocosmeticsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be also highlighted that this innovative hair dye possessed three additional features: strong adhesion capacity, as it faded only slightly after 30 washes, thermal insulation performance and incredible antibacterial performance. Differently from the previous approaches, Battistella et al suggested a metal-free PDA-based long-lasting hair coloration method was, which was not only cost-efficient, but also was carried out under mild conditions [ 246 ]. According to the study, PDA was efficiently deposed on human hair without the need of metal chelators or strong oxidants and different colors were achieved just by tuning the reaction conditions.…”
Section: Mnp and Nanocosmeticsmentioning
confidence: 99%
“… Schematic illustration of the synthesis of PDA NP and optical and SEM images of hair before and after treatment with the NP. Reproduced from [ 246 ], with permission from American Chemical Society, 2020. …”
Section: Figurementioning
confidence: 99%
“…[50][51][52] In addition, metal ions could play key roles in chelating with polydopamines and also with the keratin of the human hair surface. 16,33,34 As shown in Fig. 4e, the strong deposition could be attributed to the network of hydrogen bonds and metal chelation between the hair and polydopamine nanoparticles.…”
Section: The Mechanism Study Of the Pda Assemblies Depositionmentioning
confidence: 85%
“…Temporal hair coloring is widely used for the coverage of premature graying of hair (PGH) [13] and senile gray hair [14], but public concern on the potential side effects of dyes in the hair-dyeing products, such as allergic reactions and tumorigenesis [15][16][17], leads academic researchers and cosmetic companies to seek for alternatives [18][19][20][21][22][23][24][25][26][27][28]. For example, a mixture of graphene sheets, vitamin C, and chitosan was utilized for the black hairdyeing formulation that had an antistatic property and enhanced thermal conduction [18].…”
Section: Introductionmentioning
confidence: 99%